Power system event detection using Teager Kaiser Energy Operator and autoencoder based algorithm - Philip, Joice G.; Wendha, Brigitta; Jung, Jaesung (Energy Reports, 2024)
As the global demand for electricity increases, modern power systems are operating closer to their stability limits. This increases power system events that vary in intensity. It is essential to detect these power system events as early as possible and to take the necessary control actions to prevent escalation. This paper proposes a power system event detection method based on the Teager Kaiser Energy Operator (TKEO) and Autoencoder. In the proposed method, the rules-based algorithm performs primary detection, and the detected events are confirmed using the TKEO and autoencoder-based algorithms. The effectiveness of the proposed method was tested using test signals, simulated power system signals, and real-time power system data obtained from an actual power system. The results reveal the robustness and accuracy of the proposed method in detecting single and multiple power system events in the PMU data.
Keywords: Auto encoders; Energy operators; Events detection; Global demand; LSTM network; Phasor measurement unit; Phasors; Power; Stability limit; Teager kaiser energy operator; Autoencoder; Event detection; LSTM network; Phasor measurement units (PMU); Teager Kaiser Energy Operator (TKEO)